2020
DOI: 10.1080/09168451.2020.1792268
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of fat oxidation during the active phase and suppression of body weight gain in glycerol-3-phosphate dehydrogenase 1 deficient mice

Abstract: We investigated whether the deletion of glycerol-3-phosphate dehydrogenase (GPD) 1 would affect carbohydrate oxidation, fat oxidation, and body weight by using the GPD1 null mice (BALB/cHeA (HeA)). We found that fat oxidation in HeA mice was significantly high during the early active phase than in BALB/cBy (By) mice used as a control under ad libitum conditions. Metabolic tracer experiment revealed that fatty acid oxidation in the skeletal muscle of HeA mice tended to be high. The energy expenditure and fat ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This enzyme catalyzes the reversible conversion of dihydroxyaceton phosphate (DHAP) to glycerol-3-phosphate (G3P) by oxidizing NADH to NAD+. Since GPD1 connects glycolysis to lipid metabolism (Sato et al, 2020) oligodendrocytes may benefit from coupling the regeneration of NAD + to the generation of G3P as a phospholipid precursor in lipid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This enzyme catalyzes the reversible conversion of dihydroxyaceton phosphate (DHAP) to glycerol-3-phosphate (G3P) by oxidizing NADH to NAD+. Since GPD1 connects glycolysis to lipid metabolism (Sato et al, 2020) oligodendrocytes may benefit from coupling the regeneration of NAD + to the generation of G3P as a phospholipid precursor in lipid biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme catalyzes the reversible conversion of dihydroxyaceton phosphate (DHAP) to glycerol‐3‐phosphate (G3P) by oxidizing NADH to NAD+. Since GPD1 connects glycolysis to lipid metabolism (Sato et al, 2020) oligodendrocytes may benefit from coupling the regeneration of NAD + to the generation of G3P as a phospholipid precursor in lipid biosynthesis. Cytosolic GPD1 in oligodendrocytes may thus provide an additional way to make NAD+ regeneration partly independent from the action of mitochondrial NADH shuttles and may thus substitute for the lack of LDH reaction in oligodendrocytes to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the metabolite alterations (in G3P, DHAP, and the lactate/pyruvate ratio), the exercise tolerance and pancreatic islet function of the mutant mice were normal. On the other hand, later studies revealed that mice without GPD1 had higher fatty acid oxidation in skeletal muscle, leading to higher exercise endurance and less weight gain 33 , 34 , possibly regulated by EP300 interacting inhibitor of differentiation 1 (EID1) 35 . Although other roles of GPD1, such as protection from cell death upon treatment with oxidants, have been reported with a cell line 36 , 37 , confirmation is necessary in in vivo systems.…”
Section: Glycerol 3-phosphate Dehydrogenases: Individual Enzymes and ...mentioning
confidence: 99%
“…Moreover, hypoxia-inducible factor 1 subunit alpha (HIF-1α) directly regulates GPD1 at the transcriptional level, thereby inhibiting mitochondrial function and lipid metabolism [ 15 ]. In addition, GPD1 deficiency induces enhanced fat oxidation and inhibits weight gain [ 16 ].…”
Section: Introductionmentioning
confidence: 99%